Choroidal Osteoma with Choroidal Neo Vascular Membrane: Doi: 10.36351/pjo.v40i2.1769 - Sivaranjani; Pragnya, Lita; D Sindal, Manavi; Saishekar, Roopa (Pakistan Journal of Ophthalmology, 2024)
Choroidal osteoma (CO) is a rare benign tumor usually unilateral and have a female preponderance. We report a case of a 34-year-old healthy malediagnosed with unilateral Choroidal Osteoma with an associated Choroidal NeoVascularMembrane(CNVM).Thediagnosiswasconfirmedbasedonclinicalexamination, typical findings on B-scan, Fundus fluorescein angiography,Indocyanine green angiography and Optical coherence tomography. The CNVMwas treated with intravitreal Bevacizumab injections and showed a good responseinitially.TherewasarecurrenceofCNVMovertwoyearswhenpatientwaslosttofollow-up. Treatmentwith intravitreal Ranibizumab bio similar injection helpedstabilize hisvision. Regular follow-up is essential for timely treatment ofrecurrenceof CNVMand optimum visualoutcomes.